Alien invasive plants in Schuinsdraai Nature Reserve : an investigation into their extent and effect - Derks, Sierk Joseph Sebastiaan (My University, 2022)
Nature reserves are reservoirs for biodiversity. Their very purpose is to preserve indigenous fauna and flora and thus protect associated ecosystem services. The Schuinsdraai Nature Reserve of rural Sekhukhune District, Limpopo Province, is the focus of this study. Sekhukhune District is predominantly rural, with limited economic opportunities but rich mineral resources, the mining of which negatively impacts biodiversity. The Sekhukhune Centre of floristic endemism falls within this district and the nature reserve is thus an important factor in safeguarding a representative section of this floristic center. The veld type present in the reserve is central sandy bushveld. Although mining is prohibited within the reserve, invasive alien plants or (IAPs) pose as high a threat to biodiversity as does mining. The spread of IAPs in nature reserves is harder to control than mining which is prohibited outright whereas IAP spread is automatic and insidious. The management of IAPs is of concern to the government of South Africa and is an ongoing process. Rural areas and the nature reserves within them, such as the Schuinsdraai Nature Reserve, are often under studied or under managed with regards to IAPs. This study supplements the available but scarce data on IAPs for Schuinsdraai Nature Reserve. The Schuinsdraai Nature Reserve is dominated by the Central Sandy Bushveld vegetation type. Rainfall is on average 470 mm per year and mean annual temperature varies from 24 ˚C in the summer, to 14 ˚C in the winter. The topography includes mountains, hills, plains, and the Flag Boshielo Dam. The aims of the study were to establish the presence and extent of IAPs in the Schuinsdraai Nature Reserve and to determine whether the IAPs present negatively affect the biodiversity. Road-side inspections, road surveys and line transects were used to investigate presence and extent of IAPs. Modified Braun-Blanquet quadrates were used to compare the effect of the most prevalent IAPs on the plant biodiversity in the Schuinsdraai Nature Reserve. Quadrates were positioned in areas heavily infested by species of IAPs and these areas compared with untransformed areas within 10 m of the infested quadrates. Species richness, species evenness and v biodiversity indices were calculated for transformed (control) areas compared with infested areas. Roadside inspections and road surveys indicated the presence of IAPs. They revealed that most IAPs were present on the eastern side of the nature reserve closest to areas most visited by tourists. Roads and the movement of people therefore affect the spread of IAPs within the Schuinsdraai Nature Reserve. The four most prevalent species identified from roadside inspections and road surveys were: Opuntia stricta, Cylindropuntia fulgida, Cereus jamacaru and Boerhavia diffusa. Opuntia stricta had the greatest negative effect and was also the most prevalent IAP on the Schuinsdraai Nature Reserve. The number of IAPs per transect observed in the area where access was unlimited was significantly higher than where access was limited. Opuntia stricta was the IAPs exhibiting the most significant (.00057) impact on species richness and species diversity and, where funds are limited, these should be targeted for eradication rather than other IAPs. From the results obtained, management recommendations were tabled including the most important, which is to clearly demarcate areas where public movement should be restricted, and meticulously patrol areas which are open to the public and remove IAP’s immediately. In conclusion, IAPs are present and do cause deleterious effects on species richness, diversity and evenness within the Schuinsdraai Nature Reserve, however, the strict management of anthropogenic influences should be implemented to control their spread and increase.
Thesis (M. Sc. (Botany)) -- University of Limpopo, 2022
Keywords: Invasive plants; Schuinsdraai Nature Reserve; Biodiversity; Sekhukhune District; Invasive plants -- Biological control; Biodiversity